FACEBOOK AND THE WAY IT IS USED BY LOWER SECONDARY SCHOOL PUPILS - MIKESOVA, Jana (Trends in education, 2016)
The article describes the largest social network in the world - Facebook. Registration for this social network is compulsory. Everyone who is more than 13 years old can register. Facebook is used to communicate between users, sharing multimedia data, maintaining relationships and also for entertainment. The article also presents the results of a research which was conducted with elementary school pupils using a structured interview.
Keywords: Internet; Facebook; socialnetworks; pupils; research; interwiev.